Synapse [large type] - James, Steven, 1969- (Center Point Large Print, 2019)
Thirty years in the future. When Kestrel Hathaway, a pastor in Cincinnati, witnesses a terror attack, she's drawn into a world of conspiracies and lies that she and Jordan, her cognizant robot, have to untangle before it's too late. With the help of counterterrorism agent Nick Vernon, she needs to stop a second, more brutal attack, that could leave thousands dead. And the clock is ticking.... -- adapted from back cover